Staffing For Foreign Affairs : Personnel Systems for the 1980s and 1990s - Bacchus, William I., 1940- (Book collections on Project MUSE., 1983)
William Bacchus warns that the American Foreign Service is in serious danger of being unable to meet changing responsibilities unless it reforms its present personnel system. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly.